2010
DOI: 10.1002/ctpp.200900014
|View full text |Cite
|
Sign up to set email alerts
|

Study of High‐Beta Plasmas in a Helical System

Abstract: Recent experiments in LHD have demonstrated reactor-relevant high β plasmas. The high beta state with the volume averaged beta of 5 % has been maintained for longer than 100 times the energy confinement time without any disastrous instability. Accumulated data and extended knowledge is a firm basis for a reactor assessment as well as comprehensive physics understanding of high β plasmas. This article addresses highlighted issues from the latest experimental observations in the LHD experiment, which are related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Application of RMP is known to stabilize the RIC mode, which is considered as a seed instability of the EIC. The original aim of RIC stabilization by RMP application is to reduce the pressure gradient of bulk plasmas at iota = 1 surface by forming a magnetic island; although it was found that the RIC could be suppressed even if an island was not formed due to the plasma response at a low RMP coil current setting [48]. Figure 12(b) shows pairs of electron line average density and RMP-coil current.…”
Section: Suppression Of the Eicmentioning
confidence: 99%
“…Application of RMP is known to stabilize the RIC mode, which is considered as a seed instability of the EIC. The original aim of RIC stabilization by RMP application is to reduce the pressure gradient of bulk plasmas at iota = 1 surface by forming a magnetic island; although it was found that the RIC could be suppressed even if an island was not formed due to the plasma response at a low RMP coil current setting [48]. Figure 12(b) shows pairs of electron line average density and RMP-coil current.…”
Section: Suppression Of the Eicmentioning
confidence: 99%
“…According to an LHD experimental study [6], resistive interchange instabilities degrade the beta value by almost 5%, and do not induce rapid discharge termination like tokamaks. In helical systems, there is a little research on the active control of MHD instabilities, where it is shown that the amplitude of the resonant magnetic fluctuation decreases with the increment of the external RMP, because the impact of the instabilities on the plasma confinement is not serious, as above-mentioned [7]. However, when we design a helical fusion reactor with more than 5% volume-averaged beta plasmas, we expect a possibility that the interchange instability in the peripheral region prevents greater improvement of the plasma confinement performance of an LHD type reactor.…”
Section: Introductionmentioning
confidence: 99%
“…In the LHD, a RMP is applied as a control knob to improve the confinement performance. For example, a RMP is applied to maintain a 'stable' detached discharge [13], to control the ELM [14] and to control the resistive interchange MHD instability [15]. Figure 1 shows the magnetic fluctuation amplitude (a) and the phase (defined by the poloidal location of the island's O-point at a toroidal cross-section) of m/n = 1/1 RMP component induced by the plasma as the function of the imposed RMP coil current.…”
Section: Introductionmentioning
confidence: 99%